Desfiando Terezas e bordando Bicudas: a menina no quintal e as dobras do seu jornal - Martins, Rosilandes Cândida (2010)
In this research, I explore the narratives of Tereza Bicuda from my repertoire of childhood memories and aesthetic experiences. Tereza Bicuda figure from a set of narratives that circulate from the colonial era to the present day in the region of Central Brazil. In a multiple perspective and connected to the context of visual culture, I seek from the personal memories and vital, my insertion into the collective life and body of elements that develop in scenic poetry to merge and create fields of dialogue for this study. The elmentos personal poetics of this research are understood and lived as a raw material for reflection with the potential for aesthetic education. The narratives of Tereza Bicuda, along with my textures of learning have been plaited into a meeting / workshop with a group of young Lahetô Circus School. These employees / ox, in a context of artistic, educational and scenic, built drawings / collages and unfolded comments embroider various shades of interpretations. This study establishes a dialogue with the notions of multiplicity (SILVA, 2004) as processes of movement and diversity; "aesthetics of everyday life" (RICHTER, 2003) with an expansion of understanding of concepts, activities, and artistic artifacts and art-educational potential of these practices; notions of "precarious" (Shohat, 2006; Bakhtin, 2008) construed as ingenuity, strength and playfulness; notions of "ethics of care" (Gilligan, 1982), which function as an experience of interconnectedness and caring relationships, and "Baroque fold "(Deleuze, 1991), which connects the three-dimensional textures, linking to the textile. Merchandising notions are constructed by mating elements of "DIY" (Kincheloe, 2007), "autoetnografia (VERSIANI, 2005) and" mapping "(ROLNIK, 2006).